(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Despite numerous efforts by government at various levels and other agencies interested in water and its safety, waterborne diseases are still a major public health and environmental concern. The huge investments in water research have not yielded the highly anticipated result, although they are worth the expenditure. There are undoubtedly major causes of the increasing prevalence of waterborne diseases in Sikanderpur Lake in Muzaffarpur, since pipe-borne water and rural people are not accessible on the surface water, which is also polluted with faecal materials. The scarcity of water and poor sanitation practise among these rural residents also play a crucial role in the proliferation of water-washed diseases on Sikanderpur Lake at Muzaffarpur. Less environmental practise that promotes intra-residential breeding of insects and other vectors leads to the increased prevalence of waterborne diseases at Muzaffarpur Lake. This study concentrates on the classification of waterborne diseases and the different approaches used in the bacteriological analysis of water.